Eco-friendly collectors in apatite froth flotation: A review - Gabriela Budemberg; Rickard Jolsterå; Saeed Chehreh Chelgani (International Journal of Mining Science and Technology)
The global reliance on phosphate rock for agriculture and other industries, coupled with chemical regulations in developed countries, has driven the search for green alternatives in apatite flotation. This review investigates eco-friendly collectors’ effectiveness in promoting sustainable mineral processing, guiding future alternatives to traditional reagents. The manuscript discussed the surface properties of apatite and its interaction with eco-friendly collectors, assessing existing fundamental studies. This study sought to: (1) define, organize, and classify “eco-friendly” collectors; (2) evaluate their effect in IEP and contact angle; (3) provide a better understanding of the adsorption behavior of the different fatty acid chains into apatite surface; (4) assess their ability to reversely and directly float apatite; (5) address gaps to achieve selectivity and process optimization. Outcomes demonstrated that fatty acids are largely applied, but other renewable sources of these reagents have been promisingly evaluated. In addition, other natural reagents have been tested, and new green synthetics have demonstrated synergistic effects when combined with fatty acids, yielding significant improvements in grade and recovery. However, collector effectiveness varies with ore characteristics, like particle size and surface properties, which remain underexplored. Future research should design tailored collectors that align with mineralogical differences to enhance selectivity.